Occurrence Download - GBIF.Org User (The Global Biodiversity Information Facility, 2015)
A dataset containing 7076 species occurrences available in GBIF matching the query: { "and" : [ "TaxonKey is Melicytus ramiflorus J.R.Forst. & G.Forst.", "Country is New Zealand", "HasGeospatialIssue is false", "HasCoordinate is true", "DatasetKey is NZ National Vegetation Survey occurrence data" ] } The dataset includes 7076 records from 1 constituent datasets; see https://api.gbif.org/v1/occurrence/download/0001963-150922153815467/datasets/export for details. Data from some individual datasets included in this download may be licensed under less restrictive terms.
Keywords: GBIF; biodiversity; species occurrences